Building the inclusive city : governance, access, and the urban transformation of Dubai (2020)
As planners, our theories, concepts, and teachings define the ways in which an architect designs a home, a transportation engineer understands streets, a social worker provides community services, and politicians shape policies and laws. In my course “Building the Inclusive City” I like to remind my impressionable students that cities are not fixed; they are evolving systems of systems. These systems transform over time. They shape and are shaped by our values. The ideas shared in this book shape the way cities, nations, and regional institutions work. In the coming pages, we will explore equity, justice, and access as fundamental values and as catalysts for innovations in sustainable urban development. The rapidly urbanizing city-state of Dubai is the stage where our story unfolds. The story of Dubai, as with any living city, continues to be written day by day. The book covers a range of events that shape the story of disability in Dubai, starting with the founding of the first specialized school for children with disabilities in the 1980s through 2013, when the city’s legal, institutional, physical, and social reforms led to the passage of Dubai Law No. 2 on the Rights of Persons with Disabilities. Now more than ever, cities around the world need to focus on access and inclusion. Poor planning excludes and devalues large swathes of people. Ineffective plans limit economic productivity. The estimated 1 billion people who live with disabilities throughout the world deserve better. My lived experience as a person with a disability drew me to equitybased planning research and equips me with a perspective that uncovers gaps in current research methodologies. This perspective helps me identify fresh approaches to building more equitable and sustainable cities.